Curiosity About Adult Life In John Grisham's A Painted House:A Developmental Psychological - Novianti, Anita (2004)
The object of the study is the novel entitled A Painted House by John Grisham. The objectives of the study are to analyze the structural element of A Painted House and to reveal the curiosity about adult life in Luke Chandler personality based on developmental psychological perspective. In conducting the study, the writer uses the developmental psychological perspective. The primary data is from the novel entitled A Painted House by John Grisham that is published in 2001 by Dell Publishing a division of Random House and the secondary data is from author biography, developmental psychology theory, theory of literature, and other books that relevant to this research. The technique of data collection is library research and the technique of data analysis is descriptive qualitative analysis. The result of the study shows that curiosity is one of general characteristics of late childhood. This curiosity is influenced by the environment around them. Luke Chandler is a seven-year-old boy that has a big curiosity. Because he lives in adult environment, his curiosity is about adult life. He wants to know about adult fight, woman's body and woman's pregnancy. It gives a big influence his personality. He becomes unscrupulous child and his personality grows up more quickly than the other children on his age.